Temporal isolation between two strongly differentiated stocks of the Greenland halibut (Reinhardtius hippoglossoides Walbaum, 1792) from the Western Barents Sea - Wojtasik, Barbara; Kijewska, Agnieszka; Mioduchowska, Monika; Mikuła, Barbara; Sell, Jerzy (Polish Polar Research, 2021)
Identification of discrete stocks of Greenland halibut is an important aspect of proper fisheries exploitation. Available literature data indicated a lack of significant inter‑area differences between Greenland halibut populations from the Northeast Atlantic. To define the population diversity, two aspects were taken into account: enzyme‑genetic diversity and the concentration of heavy metals in tissues. Seven allozyme loci variations were used to characterize the genetic structure of four populations of Greenland halibut from the Western Barents Sea region. The samples were collected from the spawning area in the period when this species took migration to spawn. The sample RH4 was significantly different from the other samples collected from the same location (RH2 and RH3) and depth for over two days. Another sample (RH8), collected from the nearby area 6 days later was similar to the samples RH2, RH3. We noticed a significant divergence between the sample RH4 and the three remaining samples, where the value of the index FST fluctuated about 0.40 and approximately 0.01 between three similar populations. This genetic fluctuation negates the thesis of a panmictic character of the Western Atlantic population. Feeding groups of Greenland halibut are moving along the Barents Sea shelf and they are exposed to different heavy metals concentrations according to the food preferences or the exact place of feeding. We identified similar concentrations of heavy metals, i.e., Zn, Cu, Cd, and Pb in all samples. Trace metal analysis of aquatic organisms from the Barents Sea can provide important information on the degree of environmental contamination, and the potential impact of seafood consumption.